2020
DOI: 10.3389/fmicb.2020.00953
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DNA Extraction Method on Variation in Human and Built Environment Microbial Community and Functional Profiles Assessed by Shotgun Metagenomics Sequencing

Abstract: Sui et al.DNA Extraction Impacts Shotgun Sequencing function. Our results will inform investigators planning microbiome studies using diverse sample types in large clinical studies. A consistent DNA extraction approach across all sample types is recommended, particularly with lower microbial biomass samples that are more heavily influenced by extraction method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 66 publications
5
36
1
Order By: Relevance
“…For the microbiome, taxa, genes, and pathways present in <5% of samples (i.e., fewer than four samples here) were excluded to filter out potentially spurious features due to sequencing or classification error ( 53 ). ICCs were calculated based on the square root of the relative abundances of the top 4 phyla (i.e., Bacteroidetes , Firmicutes , Proteobacteria , and Actinobacteria ) and 15 microbial diversity metrics (observed richness, Shannon index, and Simpson index for α-diversity and the top PCoA component [PC1] for Bray-Curtis distance and Jaccard distance for β-diversity), including 5 at the species level, 5 at the gene level, and 5 at the pathway level.…”
Section: Methodsmentioning
confidence: 99%
“…For the microbiome, taxa, genes, and pathways present in <5% of samples (i.e., fewer than four samples here) were excluded to filter out potentially spurious features due to sequencing or classification error ( 53 ). ICCs were calculated based on the square root of the relative abundances of the top 4 phyla (i.e., Bacteroidetes , Firmicutes , Proteobacteria , and Actinobacteria ) and 15 microbial diversity metrics (observed richness, Shannon index, and Simpson index for α-diversity and the top PCoA component [PC1] for Bray-Curtis distance and Jaccard distance for β-diversity), including 5 at the species level, 5 at the gene level, and 5 at the pathway level.…”
Section: Methodsmentioning
confidence: 99%
“…Several challenges have hindered the adoption of sequencing technologies in routine clinical practice for microbial keratitis, including sample collection methods that are frequently ineffective (Kaye et al, 2003) compounded by the low abundance of pathogens (Ung et al, 2020), high contamination from background host DNA or laboratory reagents (Gu, Miller & Chiu, 2019), lack of standardisation in sequencing and bioinformatics processing methods . Sampling and DNA extraction methodology significantly impact upon the downstream sequencing data in samples with low biomass (Douglas et al, 2020;Sui et al, 2020). Microbial cells within the sample must be sufficiently lysed to liberate its DNA content, and this is particularly challenging for thick-walled microorganisms whereby mechanical disruption method such as bead-beating in conjunction with heat, chemical or enzymatic treatment is required in the DNA extraction protocol (De Boer et al, 2010;Ojo-Okunola et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies evaluating different extraction platforms in terms of their viral qPCR performance have found that the choice of extraction platform has a major impact on the reliability of the diagnostic results [ 24 , 25 , 26 , 27 , 28 , 29 ]. Furthermore, nucleic acid extraction methods can also impact bacteriome profiles [ 30 , 31 , 32 ] as well as the detection of particular viruses with mNGS [ 16 , 23 , 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other potential issues related to extraction methods are sample cross-contamination (contamination from one sample to another) [ 24 , 33 , 34 ] and contamination by sequences present in the environment [ 32 , 34 ] or in the molecular biology reagents (referred to as the kitome) [ 35 , 36 , 37 ]. In viral mNGS studies, these two aspects constitute a major concern and must be precisely evaluated [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%